1979
DOI: 10.1017/s0022215100088307
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic study of rhinoliths

Abstract: Five nasal stones were extracted from five patients. The etiology and clinical picture have been discussed. The stones were analysed by a crystallographic method, using an X-ray diffraction technique. Their composition was identified as calcium phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The term rhinolith was first coined in 1845 to describe a partially or completely encrusted foreign body in the nose [11]. Calcified incrustations in the nasal cavity were subjected to a chemical analysis, first by Axmann in 1829 [12], and thereafter by various other authors [2, 11, 1317]. In general they comprise 90% inorganic material, with the remaining 10% being made up of organic substances incorporated into the lesion from nasal secretions.…”
Section: Discussionmentioning
confidence: 99%
“…The term rhinolith was first coined in 1845 to describe a partially or completely encrusted foreign body in the nose [11]. Calcified incrustations in the nasal cavity were subjected to a chemical analysis, first by Axmann in 1829 [12], and thereafter by various other authors [2, 11, 1317]. In general they comprise 90% inorganic material, with the remaining 10% being made up of organic substances incorporated into the lesion from nasal secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the field of nonlinear optics has increasingly concentrated on the design of new organometallic complexes, since the report in 1987 by Green et al, 7 in which good second‐harmonic generation (SHG) efficiency was revealed for a ferrocenyl derivative. In recent times, organometallic complexes are among the most frequently investigated materials for their nonlinear optical properties 8–14 . The optoelectronic characteristics of these materials are extremely dependent on the d electron configuration and energy levels, which can be easily modulated through the choose of metal ion and oxidation state as well as the ligand environments.…”
Section: Introductionmentioning
confidence: 99%
“…The global reactivity parameters have been listed in Table 10. The global reactivity parameters are the functions of the energy of FMO (E HOMO and E LUMO ) of the ligand/the complex 37–39 . The ground state energy of the synthesized complex Me 2 SnL (4) /Me 2 Sn(SCM) (Complex 4) is lower than its corresponding ligand L (4) H 2 /SCM.…”
Section: Resultsmentioning
confidence: 99%